Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.14712/18059694.2020.13
|View full text |Cite
|
Sign up to set email alerts
|

Association of PAI-1 rs1799889 Polymorphism with Susceptibility to Ischemic Stroke: a Huge Meta-Analysis based on 44 Studies

Abstract: Background: the PAI-1 rs1799889 polymorphism has been reported to be associated with susceptibility to ischemic stroke. However, the results of previous studies have been inconsistent or controversial. Hence, we performed a systematic review and meta-analysis to evaluate the association of PAI-1 rs1799889 polymorphism with ischemic stroke risk. Methods: A comprehensive literature search was performed on PubMed, Web of Science, Scopus, SciELO, CNKI, and CBD databases up to November 05, 2019. Pooled odds ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Finally, 39 case-control studies including 7 studies with 2005 cases and 2,748 controls were on PON1 rs662, 6 studies with 2,031 cases and 1,973 controls on PON1 rs854560, 12 studies with 3,444 cases and 3,583 controls on LEP rs7799039, and determined by Z-test, in which P<0.05 was considered statistically significant. The associations was evaluated under all five genetic models, i.e., allele (B vs. A), homozygote (BB vs. AA), heterozygote (BA vs. AA), dominant (BB+BA vs. AA), and the recessive (BB vs. BA+AA), in which ''B'' presents mutant and ''A'' wild allele (Jafari-Nedooshan et al, 2019;Jafari et al, 2020). Between-study heterogeneity was estimated using a Cochran-based Q statistical test, with P-values less than 0.1 indicated the absence of indicated heterogeneity among studies.…”
Section: Selected Studies Characteristicsmentioning
confidence: 99%
“…Finally, 39 case-control studies including 7 studies with 2005 cases and 2,748 controls were on PON1 rs662, 6 studies with 2,031 cases and 1,973 controls on PON1 rs854560, 12 studies with 3,444 cases and 3,583 controls on LEP rs7799039, and determined by Z-test, in which P<0.05 was considered statistically significant. The associations was evaluated under all five genetic models, i.e., allele (B vs. A), homozygote (BB vs. AA), heterozygote (BA vs. AA), dominant (BB+BA vs. AA), and the recessive (BB vs. BA+AA), in which ''B'' presents mutant and ''A'' wild allele (Jafari-Nedooshan et al, 2019;Jafari et al, 2020). Between-study heterogeneity was estimated using a Cochran-based Q statistical test, with P-values less than 0.1 indicated the absence of indicated heterogeneity among studies.…”
Section: Selected Studies Characteristicsmentioning
confidence: 99%
“…The human PAI-1, a serine protease inhibitor (also known as Serpin E1) is located on chromosome 7q21.3-q22, consists of 9 exons and with a length of 12.2 kb [29]. The PAI-1 promoter contains a common − 675 4G5G polymorphism that may affect both basal and inducible PAI-1 expression [30,31]. The progress in the knowledge about the role of PAI-1 gene in up regulation of hyperinsulinemia and hyperglycemia have led to several studies have tested a potential association of the PAI-1 4G5G polymorphism with development of DR and DN in diabetic patients [32], but the results were conflict.…”
Section: Introductionmentioning
confidence: 99%
“…PAI-1 rs1799889 4G/5G polymorphism (4G vs. 5G) has been associated with an increased risk of DVT, MI and ischemic stroke. 54) 55) 56) …”
Section: Racial Differences In Thrombogenicity Componentsmentioning
confidence: 99%
“…The significant linkage of PAI-1 rs1799889 polymorphism (4G vs. 5G) to the risks of DVT, CAD and ischemic stroke was more prominent in the Asian population. 55) 56) Limited studies have also identified lower levels of circulating protein C and protein S, and endogenous anticoagulants in African Americans. 59) 60) …”
Section: Racial Differences In Thrombogenicity Componentsmentioning
confidence: 99%